Effects of reducing exposure to air pollution on submaximal cardiopulmonary test in patients with heart failure: Analysis of the randomized, double-blind and controlled FILTER-HF trial. (15th July 2016) - Vieira, Jefferson L.; Guimaraes, Guilherme V.; de Andre, Paulo A.; Saldiva, Paulo H. Nascimento; Bocchi, Edimar A.
Abstract: Background: Air pollution exposure could mitigate the health benefits of exercise in patients with heart failure (HF). We tested the effects of a respiratory filter on HF patients exposed to air pollution during exercise. Methods and Results: Ancillary analysis of the FILTER-HF trial, focused on the exercise outcomes. In a randomized, double-blind, 3-way crossover design, 26 HF patients and 15 control volunteers were exposed to clean air, unfiltered dilute diesel engine exhaust (DE), or filtered DE for 6 min during a submaximal cardiopulmonary testing in a controlled-exposure facility. Prospectively collected data included six-minute walking test [6mwt], VO2, VE/VCO2 Slope, O2 Pulse, pulmonary ventilation [VE], tidal volume, VD/Vt, oxyhemoglobin saturation and CO2-rebreathing. Compared to clean air, DE adversely affected VO2 (11.0 ± 3.9 vs. 8.4 ± 2.8 ml/kg/min; p < 0.001); 6mwt (243.3 ± 13.0 vs. 220.8 ± 13.7 m; p = 0.030); and O2 Pulse (8.9 ± 1.0 vs. 7.8 ± 0.7 ml/beat; p < 0.001) in HF patients. Compared to DE, filtration reduced the particulate concentration from 325 ± 31 to 25 ± 6 μg/m 3, and was associated with an increase in VO2 (10.4 ± 3.8 ml/kg/min; p < 0.001 vs. DE) and O2 Pulse (9.7 ± 1.1 ml/beat; p < 0.001 vs. DE) in patients with HF. Filtration was associated with higher VE and CO2 -rebreathing in both groups. VE/VCO2 Slope was higher among patients with HF. Conclusion: DE adversely affects exercise capacity in patients with HF. A simple respiratory filter can reduce the adverse effects of pollution on VO2 and O2 Pulse. Given the worldwide prevalence of exposure to traffic-related air pollution, these findings are relevant for public health especially in this highly susceptible population. The filter intervention holds great promise that needs to be tested in future studies.